The ghost & Mrs. Muir - Mankiewicz, Joseph L.; Tierney, Gene.; Harrison, Rex.; Sanders, George, 1906-1972. ([United States] : 20th Century Fox, 1947)
Time: The turn of the century. Determined to make a life for herself and her daughter, Lucy Muir (Tierney), a young widow, moves into a cottage overlooking the windswept English coast. She soon learns that it's haunted by the ghost of its former owner, a salty sea captain (Harrison). But the Captain's effort to scare off his new tenant soon develops into a love affair.
Special features: Audio commentaries by Greg Kimble, Christopher Husted, Jeannie Bassing and Kenneth Geist ; "Rex Harrison, the Man Who Would Be King" as seen on A & E ; still gallery ; theaterical trailer.
From the novel by R.A. Dick.
Starring: Gene Tierney, Rex Harrison, George Sanders.
Rated NR.
DVD.
In English, French, or Spanish with optional English or Spanish subtitles.
Closed-captioned.
Keywords: Ghost plays; Mothers and daughters -- Drama; England -- Drama; Feature films